Long‐Term Extracorporeal Membrane Oxygenation as Bridging Strategies to Lung Transplantation in Rapidly Devastating Isolated Langerhans Cell Histiocytosis. Issue 5 (3rd February 2016) - Sacco, Oliviero; Moscatelli, Andrea; Conte, Massimo; Grasso, Chiara; Magnano, Gian Michele; Sementa, Angela Rita; Martelli, Alberto; Rossi, Giovanni A.
Abstract : Isolated pulmonary involvement in pediatric Langerhans cell histiocytosis (LCH) is extremely rare. While the multisystem‐LCH course varies from spontaneous remission to rapid deterioration with lethal outcome, single system involvement is generally associated with favorable prognosis. A child with isolated pulmonary LCH had an extremely rapid progression leading to respiratory failure, despite treatment with prednisone and vinblastine. Since lung hyperinflation and cystic degeneration contraindicated conventional mechanical ventilation, extracorporeal membrane oxygenation (ECMO) was chosen for 50 days as a bridge to lung transplantation. The mechanisms involved in disease progression and the usefulness of long‐term ECMO are discussed.